Comparison of step-wise and ramp-wise incremental rowing exercise tests and 2000-m rowing ergometer performance - Ingham, S. A.; Pringle, J. S.; Hardman, S. L.; Fudge, B. W.; Richmond, V. L. (International Journal of Sports Physiology and Performance, 2013)
Purpose: This study examined parameters derived from both an incremental step-wise and a ramp-wise graded rowing exercise test in relation to rowing performance. Methods: Discontinuous step-wise incremental rowing to exhaustion established lactate threshold (LT), maximum oxygen consumption (VO2maxSTEP), and power associated with VO2max (W VO2max). A further continuous ramp-wise test was undertaken to derive ventilatory threshold (VT), maximum oxygen consumption (VO2maxRAMP), and maximum minute power (MMW). Results were compared with maximal 2000-m ergometer time-trial power. Results: The strongest correlation with 2000-m power was observed for MMW (r = .98, P < .001), followed by W VO2max (r = .96; P < .001). The difference between MMW and W VO2max compared with the mean of MMW/W VO2max showed a widening bias with a greater difference coincident with greater power. However, this bias was reduced when expressed as a ratio term and when a baseline VO2 was accounted for. There were no differences (P = .85) between measures of VO2maxSTEP and VO2maxRAMP; rather, the measures showed strong association (r = .97, P < .001, limits of agreement = -0.43 to 0.33 L/min). The power at LT and VT did not differ (P = .6), and a significant association was observed (r = .73, P = .001, limits of agreement = -54.3 to 20.2 W, SEE = 26.1). Conclusions: This study indicates that MMW demonstrates a strong association with ergometer rowing performance and thus may have potential as an influential monitoring tool for rowing athletes.